Significance of serum-pleural effusion albumin gradient in differentiating transudative and exudative pleural effusions in comparison to light’s criteria - G., Sujatha; P., Vindhya; K., Kalyan Kumar (International Journal of Advances in Medicine, 2017)
Background:Approximately one million patients develop pleural effusion every year. It is a common clinical disorder and is either a manifestation or a complication of one or other respiratory or non-respiratory disorders. It leads to serious prognosis, if not diagnosed and treated properly. To calculate SEAG and Light’s criteria and to compare SEAG with Light’s criteria in analyzing pleural effusions. Methods: A total of hundred patients were selected for the study. Pleural fluid of patients who met the inclusion and exclusion criteria were collected, when pleural fluid is being tapped for diagnostic thoracocentesis. Venous blood sample was collected along with diagnostic thoracocentesis or within 24 hours of thoracocentesis. Written informed consent was obtained from them for thoracocentesis. Results:In our study we compared the clinical outcome with outcome as per Pleural fluid/Serum protein ratio (p value of <0.0001), pleural fluid/serum LDH (p value of <0.0001) and pleural fluid LDH (p value of <0.0001) separately and the p values were statistically significant. The sensitivity, specificity, PPV and NPV of Light’s criteria were 77.2%, 100%, 100%, 93.9% respectively. We compared Light’s criteria outcome with clinical outcome and the difference was statistically significant (p value of <0.0001). SEAG showed 100% sensitivity, 97.43% specificity, 91.6% PPV and is 91.66% and NPV is 100%. We compared the clinical outcome with SEAG and there was statistically significant difference (p value of <0.0001). We compared SEAG with Light’s criteria and the difference was statistically significant (p <0.0001). We compared Light’s plus pleural fluid protein gradient with SEAG and the difference is statistically significant (p value of <0.0001). Conclusions:SEAG is more sensitive for classifying transudates and more specific for exudates than Light’s criteria.